2015
DOI: 10.1371/journal.pone.0128265
|View full text |Cite
|
Sign up to set email alerts
|

Novel Epigenetic Changes Unveiled by Monozygotic Twins Discordant for Smoking Habits

Abstract: Exposure to cigarette smoking affects the epigenome and could increase the risk of developing diseases such as cancer and cardiovascular disorders. Changes in DNA methylation associated with smoking may help to identify molecular pathways that contribute to disease etiology. Previous studies are not completely concordant in the identification of differentially methylated regions in the DNA of smokers. We performed an epigenome-wide DNA methylation study in a group of monozygotic (MZ) twins discordant for smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 37 publications
2
47
0
1
Order By: Relevance
“…However, the average differences between cases and healthy controls were lower than 10%. Further, hypo‐methylation at F2RL3 gene was strongly associated with smoking habits (Zhang et al, ; Allione et al, ; Fasanelli et al, ), a known risk factor for CCVD, suggesting F2RL3 gene as a potential mediator in the association of smoking with CCVD (Breitling et al, ). The evidence above suggested us to consider the results of the single CpG analyses carefully.…”
Section: Discussionmentioning
confidence: 99%
“…However, the average differences between cases and healthy controls were lower than 10%. Further, hypo‐methylation at F2RL3 gene was strongly associated with smoking habits (Zhang et al, ; Allione et al, ; Fasanelli et al, ), a known risk factor for CCVD, suggesting F2RL3 gene as a potential mediator in the association of smoking with CCVD (Breitling et al, ). The evidence above suggested us to consider the results of the single CpG analyses carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation changes can be caused by external conditions, such as long-term stress exposure (Klengel et al, 2014;Romens et al, 2015), (prenatal, maternal) smoking exposure (Allione et al, 2015;Lee et al, 2015) and dietary modifications at conception (Dominguez-salas et al, 2014). There are no epigenetic studies of the association between DNA methylation and WB, but some epigenetic studies have been performed involving complex traits related to WB.…”
mentioning
confidence: 99%
“…In adult smokers, an association with DNA methylation in the AHRR gene was also observed in lymphoblasts and alveolar macrophages. 59 A recent monozygotic twin study 60 found differential methylation between the smoking and nonsmoking twins in eight loci that had been reported in prior studies, including loci in AHRR and F2RL3 . Differential DNA methylation has also been observed with respect to current vs. former smoking, cumulative smoking exposure (e.g., lifetime pack-years of smoking), and time since quitting (among former smokers).…”
Section: Lifestyle Environment Aging and Dna Methylationmentioning
confidence: 77%